Study the electrical activity of the rectus femoris and the twin muscle impact of the training curriculum to develop explosive power. - Saadoun, Saad (Journal of Physical Education, 2016)
This research included the introduction and the importance of research, which touched the researcher to use modern instruments and equipment like (EMG) Bluetooth in monitoring the work of muscles and understand the changes taking place within the muscle fibers during the work of muscles at rest and during physical effort so that we can legalize training programs for strength muscle on a right scientifically basis the research problem lies in the lack of use of modern equipment, especially the (EMG) Bluetooth in monitoring the work of muscles with coaches and specialists in action sports. The objective of this research to study changes in the electrical activity of the rectus femoris and twin muscle on the impact of training curriculum to develop explosive power. The research sample consisted of (18) trainers, the researcher used the experimental method with single experimental group design and pre posttests, the researcher used the Sergeant test (vertical jump of stability) in the course of recording the electrical activity before and after the training curriculum prepared. Through the analysis of the results statistically show changes in the form and nature of the electrical activity between the two tests pre and post can be used in the development and codification of programs and curricula training muscle strength, the researcher recommended to use (EMG) Bluetooth in monitoring the work of the muscles for use in the development and codification training programs. of training programs and curricula